OMTI Fabry-Perot interferometer wind data (630-nm aurora and airglow) at Tromsoe, Norway - Kazuo Shiokawa; Yuichi Otsuka; ISEE IUGONET Metadata Management Group (名古屋大学, 2014)
Optical Mesosphere Thermosphere Imagers (OMTIs) Fabry-Perot Interferometer (FPI) Data. The FPI measures neutral wind in the thermosphere at 200-300km altitudes through the Doppler shift of 630-nm aurora and airglow emission. For more information, see http://stdb2.isee.nagoya-u.ac.jp/omti/. Digital data are available upon request to PI. For details of the instrument, please take a look at Shiokawa, K., Y. Otsuka, S. Oyama, S. Nozawa, M. Satoh, Y. Katoh, Y. Hamaguchi, Y. Yamamoto and J. Meriwether, Development of low-cost sky-scanning Fabry-Perot interferometers for airglow and auroral studies, Earth Planets Space, vol.64, no.11, 1033-1046, 2012. dataset